Role of Mixed-Species Stands in Attenuating the Vulnerability of Boreal Forests to Climate Change and Insect Epidemics - Chavardès, Raphaël D.; Gennaretti, Fabio; Grondin, Pierre; Cavard, Xavier; Morin, Hubert; Bergeron, Yves (Frontiers in Plant Science, 2021)
We investigated whether stand species mixture can attenuate the vulnerability of eastern Canada’s boreal forests to climate change and insect epidemics. For this, we focused on two dominant boreal species, black spruce (Picea mariana [Mill.] BSP) and trembling aspen (Populus tremuloides Michx.), in stands dominated by black spruce or trembling aspen (“pure stands”), and mixed stands composed of both species within a 36 km2 study area in the Nord-du-Québec region. For each species in each stand composition type, we tested climate–growth relations and assessed the impacts on growth by recorded insect epidemics of a black spruce defoliator, the spruce budworm (Choristoneura fumiferana [Clem.]), and a trembling aspen defoliator, the forest tent caterpillar (Malacosoma disstria Hübn.). We implemented linear models in a Bayesian framework to explain baseline and long-term trends in tree growth for each species according to stand composition type and to differentiate the influences of climate and insect epidemics on tree growth. Overall, we found climate vulnerability was lower for black spruce in mixed stands than in pure stands, while trembling aspen was less sensitive to climate than spruce, and aspen did not present differences in responses based on stand mixture. We did not find any reduction of vulnerability for mixed stands to insect epidemics in the host species, but the non-host species in mixed stands could respond positively to epidemics affecting the host species, thus contributing to stabilize ecosystem-scale growth over time. Our findings partially support boreal forest management strategies that include stand species mixture to foster forests that are resilient to climate change and insect epidemics.